Muhammad Imarah's Thought on Fiqh Moderation - al-Banna, Ahmad Hasan; Rosyidah, Umi; Syafaq, Hammis (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2023)
Abstract: Modern scholars know the clash of two conflicting currents of thought, between the extreme right (tafrith) and the extreme left (ifrath) currents. This is very dangerous for Islamic civilization. Therefore, wasathiy (moderate) Islamic scholars, such as Muhammad Imarah (1931-2020) seek to direct Muslims to understand and implement the teachings of wasathoy Islam. This article discusses Muhammad Imarah's thoughts on the fiqh of moderation. This research is literature and qualitative. Data collection is carried out through a literature review and analyzed descriptively. The results of the study concluded that about moderation fiqh, Muhammad Imarah argued that moderate ijtihad needs to be developed for now. Muhammad Imarah stated that the relationship between text and ijtihad is always side by side (al-talazum wa al musahabah daiman wa abadan), there is a text, there is ijtihad and ijtihad departs from the text, and ijtihad is to peel the meaning contained in a text to decide the fiqh law of the text. The fiqh verdict is subjective because it takes the form of conjecture (al-dhan).